Consensus or dissensus? Analysing people's perceptions of the necessities of life in Finland - Mäkinen Lauri (Policy Press, 2025)
The aim of this study is to analyse whether or not people are in consensus on what the necessities of life are in Finland. Consensus is analysed through two criteria: a public oriented view on the necessities and agreement between individuals. The study utilises a Finnish postal survey from 2015 where people were asked about the necessity of 23 items. The results suggest that individual views are shaped by personal circumstances and a fully public-oriented view cannot be established. Further, the respondents did not seem to agree on what are necessities. This implies that the minimum living standard could not be established consensually.